Tennis ball diameter: the effect on performance and the concurrent physiological responses - Cooke, K.; Davey, P. R. (Journal of Sports Sciences, 2005)
The aim of this study was to examine the influence of a pressurized tennis ball 6% greater in diameter (Type 3) than a standard sized (Type 2) ball on performance and the physiological responses to the Loughborough Intermittent Tennis Test (LITT) (Davey et al., 2002). Eight competitive tennis players (males, n??=??4, age 24.8?±?3.5 years, body mass 81.3?±?3.1 kg, height 1.74?±?0.02 m, estimated &Vdoti;O2max 54.4?±?2.6 ml?·?kg-1?·?min-1; females, n??=??4, age 26.3?±?3.1 years, body mass 67.0?±?6.7 kg, height 1.68?±?0.02 m, estimated &Vdoti;O2max 49.9?±?3.3 ml?·?kg-1?·?min-1; mean?±) completed two main trials of the LITT with either the Type 2 or Type 3 tennis balls to the point of volitional fatigue. The mean time to volitional fatigue was 29.5% greater during the Type 3 trials than during the Type 2 trials (56.9?±?6.4 min vs 40.1?±?3.7 min; P?<?0.05). The mean percentage accuracy and mean percentage consistency recorded for the entire LITT were greater for the Type 3 than the Type 2 trials (9.2?±?1.5 vs 4.0?±?0.3% and 61.1?±?0.6 vs 51.3?±?0.6%, respectively; P?<?0.01). A significantly lower mean heart rate and blood lactate concentration were observed during the Type 3 than during the Type 2 trials. There was a clear effect of ball diameter on tennis performance and certain physiological responses.